NUMERICAL INVESTIGATIONS OF THE ORBITAL DYNAMICS AROUND A SYNCHRONOUS BINARY SYSTEM OF ASTEROIDS - Santos, L. B.T.; de Almeida, Allan Kardec; Sousa-Silva, P. A. [UNESP]; Terra, M. O.; Sanchez, D. M.; Aljbaae, S.; Prado, A. F.B.A.; Monteiro, F. (Universidad Nacional Autonoma de Mexico, 2023)
In this article, equilibrium points and families of periodic orbits in the vicinity of the collinear equilibrium points of a binary asteroid system are investigated with respect to the angular velocity of the secondary body, the mass ratio of the system and the size of the secondary. We assume that the gravitational fields of the bodies are modeled considering the primary as a mass point and the secondary as a rotating mass dipole. This model allows to compute families of planar and halo periodic orbits that emanate from the equilibrium points L1 and L2. The stability and bifurcations of these families are analyzed and the results are compared with the results obtained with the restricted three-body problem (RTBP). The results provide an overview of the dynamical behavior in the vicinity of a binary asteroid system.
Keywords: celestial mechanics; minor planets, asteroids: general